Pengaruh Lama Berada di Sekolah (Full Day) Terhadap Personal Sosial Anak Usia Sekolah di SMP 7 Muhammadiyah Surakarta - Prawitasih, Cahyaningtyas Retno; , Endang Zulaicha, S.Kp (2017)
Background: Children of school age who is experiencing a period of growth and development of language and social relationships require wider to develop social concepts. A social personal aspects related to the ability of dependent, socialize and interact with their environment. Social personal school-age children are very dependent on the individual child, the role of parents, and the community. School a full day (full day) and school half a day (regular) could affect social personal school-age children. Personal social development at school age is how children can teract with peers, adults and society. The purpose of this study was to compare the effect of old to be in school to social personal school age children. Methods: This study used quantitative research with analytic design. case-control The sample used in this study 31 students of class A and class B program full day and 31 students of class C and D program of regular classes. The sampling technique using accidental sampling. The instruments used are social personal onnaire. The analysis is univariate and bivariate analysis using the Chi Square. Results: Of the 31 students who attend school full day (full day), students who coined social personal well reached 32.3% and students who have poor social persona as much as 67.7%. A total of 31 students who went to school half a day, students who have a good social personal as much as 90.3% and students who have poor social personal as much as 9.7%. Based on the Chi Square is known that the Asymp.Sig (2-sided) of .016 smaller than α = 0:05. Conclusion: School-age children who attend school half a day had a two and a half times better social personal than students who attend school full day (full day). The existence of a significant impact on long in school (full day) on social personal in junior high school-age children 7 Muhammadiyah Surakarta.